2005
DOI: 10.1085/jgp.200509380
|View full text |Cite
|
Sign up to set email alerts
|

Long Polyamines Act as Cofactors in PIP2 Activation of Inward Rectifier Potassium (Kir2.1) Channels

Abstract: Phosphatidylinosital-4,5-bisphosphate (PIP2) acts as an essential factor regulating the activity of all Kir channels. In most Kir members, the dependence on PIP2 is modulated by other factors, such as protein kinases (in Kir1), Gβγ (in Kir3), and the sulfonylurea receptor (in Kir6). So far, however, no regulator has been identified in Kir2 channels. Here we show that polyamines, which cause inward rectification by selectively blocking outward current, also regulate the interaction of PIP2 with Kir2.1 channels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Inhibition of Kir2.3 currents was significantly reduced by a single point mutation of (I213L), which enhances channel interaction with membrane PIP 2 . More recently, it was found that long polyamines were capable of strengthening the PIP 2 -channel interaction (Xie et al, 2005). In the present work, pretreatment with spermine (100 M) decreased the inhibitory effect of tamoxifen on Kir2.1, perhaps by strengthening the channel interaction with PIP 2 (Xie et al, 2005).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Inhibition of Kir2.3 currents was significantly reduced by a single point mutation of (I213L), which enhances channel interaction with membrane PIP 2 . More recently, it was found that long polyamines were capable of strengthening the PIP 2 -channel interaction (Xie et al, 2005). In the present work, pretreatment with spermine (100 M) decreased the inhibitory effect of tamoxifen on Kir2.1, perhaps by strengthening the channel interaction with PIP 2 (Xie et al, 2005).…”
Section: Discussionsupporting
confidence: 65%
“…More recently, it was found that long polyamines were capable of strengthening the PIP 2 -channel interaction (Xie et al, 2005). In the present work, pretreatment with spermine (100 M) decreased the inhibitory effect of tamoxifen on Kir2.1, perhaps by strengthening the channel interaction with PIP 2 (Xie et al, 2005). In support of this hypothesis, pretreatment or continuous application of PIP 2 markedly decreased the inhibition induced by tamoxifen, 4-hydroxy-tamoxifen (data not shown), and raloxifene (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of Kir6.2 currents by tamoxifen was significantly reduced by a single point mutation (C166S). The mutation C166S has been proposed to alter the orientation of the channel's cytoplasmic region in such a way to enhance the R176/ R177-PIP 2 interaction, resulting in bursts of openings (18,29). Additional and direct support of the hypothesis that tamoxifen may be interfering with PIP 2 -channel interaction was that continuous application of PIP 2 markedly decreased the inhibition induced by tamoxifen.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this possibility has not been considered in the literature so far. However, it was reported that PAs may stabilize the binding of other cofactors essential for the ion channel activity, such as PIP 2 for Kir and plant Shaker K + channels (Liu et al, 2005a;Xie et al, 2005). Thus, the precise biophysical mechanisms of this synergism between PAs and ROS interaction warrant a separate investigation.…”
mentioning
confidence: 99%